Motivational interviewing to enhance nicotine patch treatment for smoking cessation among homeless smokers: a randomized controlled trial. (19th March 2013) - Okuyemi, Kolawole S.; Goldade, Kate; Whembolua, Guy‐Lucien; Thomas, Janet L.; Eischen, Sara; Sewali, Barrett; Guo, Hongfei; Connett, John E.; Grant, Jon; Ahluwalia, Jasjit S.; Resnicow, Ken; Owen, Greg; et al.
Abstract Aims To assess the effects of adding motivational interviewing (MI) counseling to nicotine patch for smoking cessation among homeless smokers. Design Two‐group randomized controlled trial with 26‐week follow‐up. Participants and setting A total of 430 homeless smokers from emergency shelters and transitional housing units in Minneapolis/St Paul, Minnesota, USA. Intervention and measurements All participants received 8‐week treatment of 21‐mg nicotine patch. In addition, participants in the intervention group received six individual sessions of MI counseling which aimed to increase adherence to nicotine patches and to motivate cessation. Participants in the standard care control group received one session of brief advice to quit smoking. Primary outcome was 7‐day abstinence from cigarette smoking at 26 weeks, as validated by exhaled carbon monoxide and salivary cotinine. Findings Using intention‐to‐treat analysis, verified 7‐day abstinence rate at week 26 for the intervention group was non‐significantly higher than for the control group (9.3% versus 5.6%, P = 0.15). Among participants who did not quit smoking, reduction in number of cigarettes from baseline to week 26 was equally high in both study groups (−13.7 ± 11.9 for MI versus −13.5 ± 16.2 for standard care). Conclusions Adding motivational interviewing counseling to nicotine patch did not increase smoking rate significantly at 26‐week follow‐up for homeless smokers.